Assessment of the Reform of the Romanian Health Care System - Cătălin Ovidiu BABA; Alexandra BRÎNZANIUC; Răzvan M. CHERECHEȘ; Diana RUS (Transylvanian Review of Administrative Sciences, 2008)
The purpose of this introductory paper is to offer a brief description of the Public Health Care System in Romania, and to examine how it evolved, after the fall of the communist regime, from a Semashko health care system to a social health insurance system. We will explore how the regime influenced this evolution and whether we can talk about a distinct management component. It is not an exhaustive study, but rather an overview of some issues/problems that Romania has faced in the effort to modernize its health care system. We will start by defining public health and by outlining the major characteristics of a public health system, followed by a list of objectives recommended for use by the World Health Organization, to which the paper refers in examining the current issues in Romania. After this, the major reforms will be described and analyzed trying to identify how this affected the outcomes.